2014
DOI: 10.1371/journal.pone.0087238
|View full text |Cite
|
Sign up to set email alerts
|

Allo-Reactivity of Mesenchymal Stem Cells in Rhesus Macaques Is Dose and Haplotype Dependent and Limits Durable Cell Engraftment In Vivo

Abstract: The emerging paradigm that MSCs are immune privileged has fostered the use of “off-the-shelf” allogeneic MSC-based therapies in human clinical trials. However, this approach ignores studies in experimental animals wherein transplantation of MSCs across MHC boundaries elicits measurable allo-immune responses. To determine if MSCs are hypo-immunogeneic, we characterized the immune response in rhesus macaques following intracranial administration of allogeneic vs. autologous MSCs. This analysis revealed unambiguo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 54 publications
4
69
3
Order By: Relevance
“…Cells obtained via methods such as chorionic villus sampling (CVS) allow for the potential development of cell therapies that are autologous (derived from the patient's cells) to the fetus [16][17][18] . Autologous therapies are potentially preferable to allogeneic (not patient specific) therapies, as using the patient's own cells in a therapy should not elicit an immune response [19] . However, where autologous therapies are not required, allogeneic early gestation chorionic villus tissue can be an outstanding cell source for cell therapy as well.…”
Section: Introductionmentioning
confidence: 99%
“…Cells obtained via methods such as chorionic villus sampling (CVS) allow for the potential development of cell therapies that are autologous (derived from the patient's cells) to the fetus [16][17][18] . Autologous therapies are potentially preferable to allogeneic (not patient specific) therapies, as using the patient's own cells in a therapy should not elicit an immune response [19] . However, where autologous therapies are not required, allogeneic early gestation chorionic villus tissue can be an outstanding cell source for cell therapy as well.…”
Section: Introductionmentioning
confidence: 99%
“…In these conditions, an increase of the local expression of NK cells, T and B lymphocytes as well as macrophages was detected (181,201,202). In addition, a high expression level of allo-specific antibodies was demonstrated in the recipient hosts (202). It has been proposed that Th1 response evident by increase of IFN-was responsible for the suppression of the bone growth (181).…”
Section: Msc-immune Cell Interactions; Therapeutic Implications mentioning
confidence: 99%
“…Additionally, the chondrogenic potential of synovial MSCs transplanted into allogeneic rat with anterior meniscus defect was impaired relative to autogenic implants (201). In these conditions, an increase of the local expression of NK cells, T and B lymphocytes as well as macrophages was detected (181,201,202). In addition, a high expression level of allo-specific antibodies was demonstrated in the recipient hosts (202).…”
Section: Msc-immune Cell Interactions; Therapeutic Implications mentioning
confidence: 99%
“…Several studies, in which MSCs were used for bone and cartilage repair, have indicated that the failure of therapeutic effect of allogeneic MSCs was associated with signs of activated immune responses [115,[133][134][135]. However, in other studies where the allogeneic MSCs were loaded into scaffolds, an inflammatory response was similar to that induced by autologous MSCs with better outcomes [136][137][138][139][140][141].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%